The Effect of Customer Relationship Management on Customer retention in Private Higher Education Institute in Malaysia (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2018)
This research is conducted in order to evaluate the purpose of studying the customer relationship practices and customer satisfaction in PHEI that offers undergraduate degrees in Malaysia.  According to the results obtained, it proves that CRM practices contain more positive effect on its customer satisfaction. The sample size used was only focused on PHEI that offer undergraduate programmes in Malaysia.  According to the research conducted, there are few limitations that disclose the exact relationship between CRM and Customer Satisfaction. Education industry has become one of the major growing industries in Malaysia with various numbers of competitors. Thus, this study allows policy makers of PHEI to focus and implement CRM practices that would have an increase of direct positive impact of satisfaction for their customers.  The study conducted also helps to evaluate not only CRM and satisfaction but also evaluate the effect of the Gender and Age Group factors that reflects on the relationship.